Is endoscopy beneficial in pediatric laparoscopic gastrostomy insertion; A 9-year comparative study - Bitar, Rana; Syed, Ajia; Azaz, Amer; Rawat, David; Hobeldin, Mohamed; Miqdady, Mohamad; Abdelsalam, Seifeleslam (Frontiers in Pediatrics, 2022)
Abstract: Objectives: Advancements in pediatric percutaneous endoscopic gastrostomy placement (PEG), laparoscopic assisted gastrostomy (LAG) technique, and laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) procedure have opened up new options for gastrostomy tube placement. LAPEG utilizes endoscopy and laparoscopy for gastrostomy insertion. This review compares the outcomes and complications of LAG and LAPEG techniques in children. Methods: All LAG and LAPEG gastrostomy tube placements in children from September 2010 to September 2019 were reviewed retrospectively. Patient demographic, along with procedural and 1-year complication data, were collected. Results: 92/181 of gastrostomies were LAG and 89/181 were LAPEG. The mean age, weight and patient characteristics were comparable. Conversion rate was 1% in both groups (p=0.74), there was no peritoneal leak in either group, a minor serosal injury to the stomach was seen in 1 patient in LAG with no bowel injury in LAPEG cohort (p =0.51), need for re-operation was 1% and 2% in LAG and LAPEG respectively (p =0.49), early tube dislodgement was in 8 (9%) patients in LAG and 7 (6%) in LAPEG (p =0.53) and wound infection was 13/92 in LAG and 11/89 in LAPEG (p =0.8). The median operative time for LAPEG was less than LAG (p <0.001) by 11 minutes but the median length of hospital stay was not significantly different (p < 0.096). Conclusions: Both LAG and LAPEG techniques in children are safe with comparable complication rates and length of hospital stay, the addition of endoscopy to LAG allowed for shorter operative time in the LAPEG technique.